Recognizing Human Emotional State from a Machine - Zahoor, Saniya (International Journal of Computer Sciences and Engineering, 2019)
Emotion recognition is an approach to detect and analyze different human emotions from their facial expressions. We, humans, have versatile and consistent abilities through variable among individuals in detecting emotions, but the highspeed computer/ machines lag humans in this capability. Here, an approach is developed which will make the machines detect human emotions and learn to behave with them by analyzing their emotions. In this paper, computer vision techniques are used for feature extraction and machine learning tools and Artificial Intelligence tools for training purposes. This paper proposes a neural network based solution combined with image processing in classifying the universal emotions – Happiness, Sadness, Anger, Disgust, Surprise, and Fear.